What Drives Women Participation in Vulnerable Jobs? An Empirical Analysis in Indonesia - Wildan Syafitri; Axellina Muara Setyanti (Buletin Ekonomika Pembangunan, 2026)
Introduction/main objective: Gender disparities in Indonesia’s labor market continue to be a pressing issue, with women more likely to be engaged in informal employment lacking job security and benefits. This study aims to examine the structural and spatial factors that contribute to women’s informal employment vulnerability. Novelty: While previous studies have highlighted gendered labor segmentation, few have investigated how digital access, household roles, and financial inclusion interact to shape informality risks among women across rural and urban regions. Contribution: This paper fills a theoretical and empirical gap by applying a gendered and spatially disaggregated analysis to informality, incorporating multidimensional indicators that reflect human capital, digital capability, care burden, and financial access. Research method: The study uses binary logistic regression on microdata from the 2022 National Labor Force Survey (Sakernas), involving 400,009 female workers, to estimate the likelihood of informal employment based on education, ICT use, household demographics, and credit access, across rural and urban settings. Findings/results: Results show that digital access and higher education reduce the probability of informality, while large household size, presence of young children, and house ownership increase it. Credit access is associated with higher informality, particularly in rural areas, indicating its role in supporting informal enterprises rather than formal employment transitions. Conclusion: Findings highlight the need for gender-responsive and regionally targeted policies that expand digital infrastructure, childcare support, and formalization-linked financial services to reduce women’s labor market vulnerability in Indonesia.